Fuentes de financiamiento y su relación con el gasto operativo del Banco Central De Reserva Del Perú periodo 2019–2023 - Reategui Echevarria, Valeria (2024)
The Central Reserve Bank of Peru (BCRP) has managed its budget with significant variations in the execution of its financial resources during the period from 2019 to 2023. The objective of this study was to identify the relationship between funding sources and the BCRP's operating expenses during this period, utilizing a quantitative observational non-experimental design to analyze historical data without intervening in the variables. The results showed that the BCRP's total funding increased from S/ 447,301,426 in 2019 to S/ 516,241,190 in 2023, indicating an improved capacity to attract and manage financial resources. The composition of operating expenses revealed that personnel expenses accounted for 42%, goods and services 40%, other current expenses 15%, and capital expenses 3%, suggesting a higher investment in human resources and essential services. The average execution rate of operating expenses was 79%, with personnel expenses reaching 84%, goods and services 81%, other current expenses 98%, and capital expenses only 26%, highlighting the need to improve the planning and execution of investment projects. Operating expenses increased from S/ 354,490,822 in 2019 to S/ 416,247,678 in 2023, reflecting an expansion in operational activities and the need for more resources. However, no statistically significant relationship was found between funding sources and operating expenses, suggesting that other factors might be influencing budget management and execution. These conclusions underscore the importance of optimizing budgeting and execution processes to improve the BCRP's operational efficiency and ensure more effective use of financial resources.